Contagious zombies - Christian Bittner; Falko Fecht; Co-Pierre Georg (Deutsche Bundesbank, 2021)
Does banks' zombie lending induced by unconventional monetary policy also allow zombie firms to leverage their trade credit borrowing? We first provide evidence suggesting that - even in Germany - particularly weak banks used the European Central Bank's very long-term refinancing operations (VLTROs) to evergreen exposures to zombie firms, which in turn elevated credit risk. Second, we show that zombie firms, which obtained additional funding from banks relying to a larger extent on VLTRO funding, also increased their accounts payable and advance payments received from downstream and upstream firms. And third, zombie firms that obtained further bank funding and such trade credit after the VLTROs had an elevated expected default probability even compared to average zombie firms. This suggests that suppliers relying on banks' lending decisions as a signal about borrowers' credit quality might be misled by banks' zombie lending to extend more trade credit to zombie firms exposing suppliers to elevated contagion risk.
Keywords: G1; G20; E58; 330; unconventional monetary policy; zombie lending; trade credit